Selección de cepas de levaduras productoras de enzimas pécticas - Martos, María Alicia (2007)
The present study was undertaken to find yeast strains with high pectinolytic activity. Yeast strains isolated from citrus fruits, were screened for pectinase production. The species with the best pectinase activity was selected to evaluate their ability to produce pectic enzymes by submerged fermentation processes. The effect of different carbon sources on polygalacturonase (PGase) production was studied. Different vegetable tissues were used for tests of maceration with the crude enzyme extract. Among 154 yeast strains isolated, yeast Nº 111 was positive for pectinase activity and was identified as Geotrichum sp. Maximum PGase production obtained was 90.7 EU/ml when this yeast grown in shake flasks under the presence of glucose and citrus pectin as carbon sources. All tissues studied were macerated by the enzyme extract, microscopic examination showed a suspension of loose single cells. Lysis of cells was not observed.